The Development of Ukrainian Singing Culture during the Middle Ages - Lyudmyla M. Sbitnieva; Olena F. Sbitnieva (Anastasis: Research in Medieval Culture and Art)
The purpose of this article is to study the development of Ukrainian singing culture during the Middle Ages. Ukraine has always been famous for its songs and singers. Ukrainian singing culture dates back to ancient times. Ancient cultural monuments confirm that folk songs and folk art have played a significant role in the life of the Ukrainian people. Starting from the 10th century, church music began to develop, and thus great importance was attached to musical education. Song creativity is the most popular form of folk art, which influenced the development of many genres of Ukrainian music during the Middle Ages.